Responses of soil labile organic carbon stocks and the carbon pool management index to different vegetation restoration types in the Danxia landform region of southwest China - Ye Xiao; Yuguang Zhang; Jiumei Long; Kang Luo; Zhigang Huang (PLoS ONE, 2025)
Soil organic carbon (SOC) is an important index for evaluating soil quality in the process of ecological restoration. It plays an important role in increasing soil carbon storage, improving soil texture, and promoting plant growth. Nevertheless, dating the variation in SOC and labile SOC fractions (LOCFs) during ecological restoration processes has not been sufficiently elucidated. To enrich our comprehension of the responses of SOC and its labile fractions to different vegetation restoration types, five vegetation restoration types were selected in the Danxia landform region of southwest China, namely, shrub (SH), bamboo forest (BF), Chinese fir forest (CFF), evergreen broad-leaved forest (EBF), and mixed coniferous-broadleaf forest (MCBF). The concentrations and stocks of SOC and LOCFs, such as dissolved organic carbon (DOC), microbial biomass organic carbon (MBC), and easily oxidizable organic carbon (EOC), and the carbon pool management index (CPMI) were investigated. Results showed that the different vegetation restoration types significantly influenced SOC stocks (P < 0.05), and the concentrations and stocks of SOC and LOCFs decreased with increasing soil depth in different vegetation types, except for MBC in BF and CFF. Additionally, BF and EBF had significantly higher total SOC stocks (92.75 t ha − 1 and 60.13 t ha − 1) compared with the three other vegetation types (26.18–47.48 t ha-1) at a depth of 0–30 cm. The largest total DOC stock was observed in EBF, while BF and EBF had significantly higher MBC and EOC stocks than SH, CFF, and MCBF (P < 0.05). Compared with SH, the CPMI increased by 49.7%, 32.9%, and 35.2% in BF, CFF, and EBF, respectively, except for the MCBF. SOC and LOCFs were closely related to soil physicochemical properties, and total nitrogen, total phosphorus and moisture had a pronounced effect on them. However, higher SOC and LOCFs stocks, and CPMI were observed in BF and EBF than in the other vegetation types. This result suggests that the two plant types exhibited better ability to sequester carbon than the other vegetation types. Overall, vegetation restoration promoted the accumulation of both SOC and its fractions, the results of which varied among the different vegetation types.